2017
DOI: 10.5296/ajfa.v9i2.11832
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Variables and Stock Market Returns in Sri Lanka

Abstract: The stock market is one of the most energetic sectors that play an important role in contributing to the wealth of the economy. It plays a crucial role in the economic growth and development of an economy which would benefit industries, trade and commerce as a whole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
4
0
4
Order By: Relevance
“…Ho (2017) analysed SMP in Malaysia and found that inflation has an inverse effect, and Lee and Brahmasrene (2018) indicated that an inverse effect of inflation rate in short term in Korea. Few studies found that inflation and share price are positively associated in Sri Lanka (Chang & Rajput, 2018;Hemamala & Jameel, 2016;Shafana, 2014;Balagobei, 2017). Controversy few studies found that INF has no significant relationship with market return (Perera, 2015;Wickramasinghe, 2011 andLakmali &Madhusanka, 2015).…”
Section: Inflationmentioning
confidence: 99%
“…Ho (2017) analysed SMP in Malaysia and found that inflation has an inverse effect, and Lee and Brahmasrene (2018) indicated that an inverse effect of inflation rate in short term in Korea. Few studies found that inflation and share price are positively associated in Sri Lanka (Chang & Rajput, 2018;Hemamala & Jameel, 2016;Shafana, 2014;Balagobei, 2017). Controversy few studies found that INF has no significant relationship with market return (Perera, 2015;Wickramasinghe, 2011 andLakmali &Madhusanka, 2015).…”
Section: Inflationmentioning
confidence: 99%
“…Berdasarkan rumusan masalah yang ada dalam penelitian ini, maka dari sini dapat disimpulkan tujuan dari penelitian ini, yakni: a. Untuk mengerti apakah tingkat suku bunga memiliki efek dengan harga saham yang terdaftar di dalam Indeks LQ45. 2017), Haque & Sarwar (2012), Linck & Decourt (2016), Oshaibat (2017), Ghosh et al (2018), Sutrisno (2017), Balagobei (2017), Barakat et al (2015), Iqmal & Putra (2020), Tangjitprom (2012), membuktikan suku bunga dan return indeks saham memiliki ikatan yang bersifat negatif yang signifikan. Ketika suku bunga naik, investor dapat mengalokasikan uang mereka untuk investasi sekuritas.…”
Section: Tujuan Penelitianunclassified
“…Sedangkan Malaysia mengalami penurunan dan kenaikan inflasi dan pada Negara Arab Saudi sempat terjadi deflasi pada tahun 2017 akan tetapi mengalami inflasi pada tahun 2018 dan Bangladesh relative memiliki inflasi pada angka 6 persen. Dari gambar 3 ini (Balagobei, 2017) dan (Laichena dan Obwogi, 2015) yang mengatakan suku bunga memiliki pengaruh positif terhadap harga saham.…”
Section: Diskusiunclassified